Maintaining natural and traditional cultural green infrastructures across Europe: learning from historic and current landscape transformations - Angelstam, Per (2021)
Context Maintaining functional green infrastruc-tures (GIs) require evidence-based knowledge about historic and current states and trends of representative land cover types. Objectives We address: (1) the long-term loss and transformation of potential natural forest vegetation; (2) the effects of site productivity on permanent forest loss and emergence of traditional cultural landscapes; (3) the current management intensity; and (4) the social-ecological contexts conducive to GI maintenance. Methods We selected 16 case study regions, each with a local hotspot landscape, ranging from intact forest landscapes, via contiguous and fragmented forest covers, to severe forest loss. Quantitative open access data were used to estimate (i) the historic change and (ii) transformation of land covers, and (iii) compare the forest canopy loss from 2000 to 2018. Qualitative narratives about each hotspot landscape were analysed for similarities (iv). Results While the potential natural forest vegetation cover in the 16 case study regions had a mean of 86%, historically it has been reduced to 34%. Higher site productivity coincided with transformation to non- forest land covers. The mean annual forest canopy loss for 2000–2018 ranged from 0.01 to 1.08%.The 16 case studies represented ﬁve distinct social-ecological contexts (1) radical transformation of landscapes, (2) abuse of protected area concepts, (3) ancient cultural landscapes (4) multi-functional forests, and (5) intensive even-aged forest management, of which 1 and 4 was most common. Conclusions GIs encompass both forest naturalness and traditional cultural landscapes. Our review of Pan-European regions and landscapes revealed similarities in seemingly different contexts, which can support knowledge production and learning about how to sustain GIs.